Predictive Power of Situational Factor and Individual Factor on Misreporting Behaviour - Ascaryan Rafinda; Agus Suroso; Timea Gal (International Review of Management and Marketing, 2020)
The aim of this research is to compare the predictive power of situational factors and individual factors on misreporting behaviour. The experiments were done to 64 undergraduate students divided into four classes. Each class got a different manipulation on situational factors such as superior's authority and social conditions. Both of them were manipulated to determine their effects on misreporting behaviour, while individual factors were measured by DIT to classify moral reasoning level. Participants attended two sessions of the experiment. The first session was conducted to measure the level of student moral reasoning. The second session measured student misreporting behaviour. The analysis was done by comparing error prediction on both factors and T-Test Independent sample was used. This research found that situational factors have smaller error prediction than individual factors. It means the situational factor is more powerful predictor than the individual factor. It's imply that organization which wants to reduce misreporting behaviour should focusing deeper to the situational factor than individual factor. Keywords: Individual Factor, Misreporting Behaviour, Situational Factor. JEL Classifications: D23, C91